Model compounds for the T state of hemoglobin. - Collman, J P (1978)
O2 binding to a series of ferrous and cobaltous "picket fence" porphyrins is reported. N-Methylimidazole and covalently attached imidazoles gives O2 binding to ferrous porphyrins with deltaH degrees =-16.2 kcal/mol (-67.7 kJ/mol) and deltaS degrees =-40 eu (standard state, 1 atmosphere O2). Similar studies with cobaltous porphyrins yield deltaH degrees =- 12.8 kcal/mol (-53.5 kJ/mol) and deltaS degrees =- 39 eu. These values match well those of myoglobin and isolated subunits of hemoglobin and their cobalt reconstituted analogues. 1,2-Dimethylimidazole has been successfully used to mimic the presumed restraint of T state hemoglobin. In direct analogy to the decreased cooperativity shown by cobalt-substituted hemoglobin, model cobalt porphyrins show a smaller decrease in O2 affinity than the analogous iron porphyrins when the axial base is hindered. Thermodynamic data are presented. The molecular mechanism of cooperativity in hemoglobin is discussed.